Evaluation of environmental and cost tradeoffs of producing energy from soybeans for on-farm use. (10th February 2019) - Adler, Paul R.; Hums, Megan E.; McNeal, Frederick M.; Spatari, Sabrina
Abstract: There has been interest in producing fuel from oil seed crops for use on farms, however little guidance is available on where this may be profitable, the extent to which greenhouse gas (GHG) emissions may be mitigated or the cost associated with that mitigation. We conduct a national analysis to evaluate the economics of on-farm processing of soybeans, the GHG mitigation potential of several on-farm uses of the oil, and the cost of achieving the mitigation. We found that significant GHG mitigation is possible when substituting soybean oil for on-farm energy use, however, often the food market has higher economic value. When we characterized the conditions and consequently, the regions where on-farm soybean processing was profitable, we found that the economics and greenhouse gas abatement potential of processing soybeans on-farm improves as farm location moves towards the coastal Atlantic and Gulf regions where the economic value of the meal is higher. Overall, we found that on-farm pressing of soybeans can add value to soybean production, but the market for the extracted oil will depend on the price of soybean meal and the market for food uses of the meal. Graphical abstract: Highlights: Substituting diesel fuel with soybean oil for on-farm use mitigates GHG emissions. Soybean oil has higher economic value in food rather than energy markets. Farm scale soybean press facilities can add economic value to soybean production. Low GHG abatement costs & high economic incentives align with soybean meal value. Economics and GHG abatement improves towards coastal Atlantic and Gulf regions.